Physician Perceptions of the Safety and Efficacy of GLP-1 Receptor Agonists: Underestimation of Cardiovascular Risk Reduction and Discrepancies with Clinical Evidence - Srikanth Krishnan; Pratyaksh K. Srivastava; Jayram Attaluri; Rebecca Nayeri; Dhananjay Chatterjee; Jay Patel; Ali Nsair; Matthew Budoff; Arash Nayeri (Journal of Cardiovascular Development and Disease)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and glucose-dependent insulinotropic polypeptide/GLP-1 receptor agonists (GIP/GLP-1 RAs) are emerging as effective treatments for obesity and cardiometabolic disease. This study evaluated physician perceptions of the safety and efficacy of semaglutide and tirzepatide through a questionnaire administered to 165 attending physicians specializing in internal or family medicine, with 122 responses received. Physicians reported an average patient weight loss of 9.22%, significantly lower than the 14.9% and 18.5% reported in the STEP and SURMOUNT trials, respectively. Estimated side effect rates (32.62%) were markedly lower than trial-reported rates (89.7% and 80.5%), while estimated discontinuation rates (8.59%) exceeded trial data. Cardiovascular benefits were perceived by 48.4% of physicians in diabetic patients, consistent with random guessing, and by only 39.3% in nondiabetic patients, significantly below random guessing expectations. These results highlight discrepancies between physician perceptions and clinical evidence, suggesting gaps in understanding regarding these agents’ efficacy and safety profiles. Addressing these gaps could enhance physician knowledge, patient adherence, and clinical outcomes.